Synthesis and Evaluation of Mutual Prodrug of Mefenamic Acid and Etodolac with Sesamol for the Treatment of Alzheimer's Disease - Krishnendu, Prayaga Rajappan; Rasheed, Shebina Pareed; Kaippollil, Vibina; Rasheed, Arun; Joy, Jibin; Suhail, Pattilthodika (Indian Journal of Pharmaceutical Education and Research)
Background: Epidemiological and clinical trial data suggest that NSAIDs can be used for managing Alzheimer's disease. This research area began with the observation of reduced incidence and progression of Alzheimer's disease in arthritic patients who are on NSAID medication. Objectives: This study focuses on the mutual prodrug of Mefenamic acid and Etodolac with Sesamol for treating Alzheimer's disease. Materials and Methods: The mutual prodrugs of NSAIDs with Sesamol were synthesized using the Steglich esterification method. These hybrids were characterized through various spectrometric and physicochemical methods, followed by pharmacological evaluation. Results: The hybrids demonstrated improved aqueous and organic solubility along with enhanced lipophilicity. In antioxidant activity tests, the Mefenamic acid prodrug had an IC50 value of 101.80, comparable to Ascorbic acid (IC50 of 102.90), while the Etodolac prodrug had an IC50 value of 97.62, indicating higher activity than the benchmark. The increasing Log p-value (Mefenamic acid prodrug- 3.63 and Etodolac prodrug- 3.72) shows that the synthesized Prodrugs are more lipophilic hence can permeate the BBB easily. Behavioral studies on Albino mice showed cognitive improvements in Alzheimer's disease-induced brains. Microscopic examination of the treated mice brain tissue revealed normal histology compared to the control group. Conclusion: These findings suggest that the prodrug strategy may enhance BBB transport characteristics and provide a neuroprotective effect on the brain, offering a promising treatment for Alzheimer's disease in arthritic patients.
Keywords: Alzheimer’s disease; Antioxidants; Mutual prodrug; Mefenamic acid; Etodolac; Sesamol; Neurodegenerative disorder